Building Resilience in Adolescence: Interface between Humanities and Health - Higa Sakuma, Tânia; de Souza Vitalle, Maria Sylvia (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
In order to discuss the importance of preventive actions to build resilience in adolescence, not only this article reviews the various concepts of resilience within a dynamic and humanistic point of view, but also it proposes new perspectives and possibilities for building resilient youth through interface and multiple actions through the areas of Health and Human Sciences.